New insights into the properties of KxNa(1-x)NbO3 ceramics obtained by hydrothermal synthesis - Ramajo, Leandro Alfredo (2014)
Different reaction conditions for the hydrothermal synthesis of KxNa(1-x)NbO3 (KNN) were studied. Samples were synthesized at 190°C in a Teflon lined autoclave and the effects of different KOH/(KOH+NaOH) ratios (0 to 0.8) and total hydroxide concentration (2 to 8N) on the microstructural and electrical properties of KNN were analyzed. A sodium rich phase with a monoclinic structure has been obtained, in which the orthorhombic phase coexists as detected by X-ray diffraction. These analyses also revealed that the x value in the KxNa(1-x)NbO3 system gradually increases with the increasing KOH/(KOH+NaOH) ratio and total hydroxide concentration. Samples with higher potassium content showed higher density and improved electrical behavior. An exhaustive characterization by Confocal Raman Microscope allowed the observation of the ferroelectric domain structure in KNN ceramics. It was established that the grain boundaries constrain the 90º domain walls in order to reduce the stress accumulated by the orthorhombic and the monoclinic phase coexistence within the KNN grains.